1995
DOI: 10.3354/meps128225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of site and season on movement frequencies and displacement patterns of juvenile sea scallops Placopecten magellanicus under natural hydrodynamic conditions in Nova Scotia, Canada

Abstract: In this study, we examine the effect of site and season (spnng vs fall) on the movement frequency and net displacement of juvenile sea scallops Placopecten magellanicus, and the relationship between the net movement direction of scallops and the near-bed current direction at 2 sites in Lunenburg Bay, Nova Scotia, Canada. At each site, a total of 150 and 100 individually marked juvenile sea scallops were released on the sea bed at 2 points (Stns 1 and 2) placed 50 m apart for the spring (March) and fall (Septem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Adult Atlantic sea scallops are known to be largely sedentary, with little to no movement reported from previous studies (Posgay ; Carsen et al. ). Additionally, any movement that does happen is thought to be random in distance and direction, and any net movement over time is likely the result of tidal currents as opposed to active habitat selection (Posgay ).…”
Section: Methodsmentioning
confidence: 93%
“…Adult Atlantic sea scallops are known to be largely sedentary, with little to no movement reported from previous studies (Posgay ; Carsen et al. ). Additionally, any movement that does happen is thought to be random in distance and direction, and any net movement over time is likely the result of tidal currents as opposed to active habitat selection (Posgay ).…”
Section: Methodsmentioning
confidence: 93%
“…However, our model assumes that predator encounter is the only cause of scallop dispersal. Immigration into a site would have been negligible, since movement of released scallops tends to resemble a diffusive process, from areas of high scallop density to areas of low density, on the relatively short time scale of a seeding trial (Cliche et al 1994, Carsen et al 1996b. E. Carsen, B. G. Hatcher, and R. E. Scheibling, unpublished data).…”
Section: Scallop-specific Aspects Of the Modelmentioning
confidence: 99%
“…Finally, we did not include immigration into a site from surrounding areas, although we allowed emigration from a site. Immigration into a site would have been negligible, since movement of released scallops tends to resemble a diffusive process, from areas of high scallop density to areas of low density, on the relatively short time scale of a seeding trial (Cliche et al 1994, Carsen et al 1996b.…”
Section: Scallop-specific Aspects Of the Modelmentioning
confidence: 99%
“…Although Gru¡ydd's (1976) laboratory study indicated an increasing tendency of Iceland scallops to swim with increasing current velocity, the di¡erences between grids in our study were not likely to be due to current velocity, as mean velocity was slightly less in the west grid where movement was markedly greater. Carsen et al (1995) suggest that local di¡erences in swimming frequency of juvenile Placopecten magellanicus may be related to di¡erences in predator abundance, as predators often induce swimming escape responses. This also appears unlikely in our study given the similarity in predator densities in the two grids (Table 3).…”
Section: Variations In Scallop Movement Between Gridsmentioning
confidence: 99%
“…The potential role of swimming in the population dynamics of C. islandica and other scallops has received little attention. Previous ¢eld studies of scallop swimming only consider adults (Posgay, 1981), evaluate dispersion of juveniles in aquaculture seeding operations (Parsons et al, 1992;Carsen et al, 1995;Hatcher et al, 1996) or examine sizerelated changes in swimming e¤ciency (Carsen et al, 1996). The only ¢eld study examining swimming in C. islandica provides an indirect estimate of daily swimming frequency in a Norwegian population, based on changes in scallop numbers in permanent quadrats (Vahl & Clausen, 1980).…”
Section: Introductionmentioning
confidence: 99%